Screening and evaluation of maize varieties for resistance to Spodoptera frugiperda - Anggria Lestami; Ummi Maysaroh; Rahmatika Alfi; Hafnes Wahyuni (Indonesian Journal of Agricultural Research, 2026)
Maize is one of the staple food crops in the world, but the entry of Spodoptera frugiperda pests has reduced national maize production. Most farmers control these pests by using pesticides that cause harm to human health and the environment, so that other environmentally friendly control alternatives are needed, namely the use of resistant varieties. This study aims to obtain maize varieties that are resistant to Spodoptera frugiperda attacks. This study used a one-factor Randomized Block Design (RBD), namely maize varieties, consisting of five varieties, namely: Bisi 2, Bisi 18, Pertiwi 3, Pioneer 32, and NK 212. Each variety was repeated five times. Based on the results of observations of vegetative and generative growth parameters, it was obtained that the NK 212 variety had the best growth and production compared to other varieties. Meanwhile, the results of observations of Spodoptera frugiperda attacks showed that Pioneer 32 was a resistant variety with the lowest attack intensity. Although the NK 212 variety showed the best growth and yield, the Pioneer 32 variety proved to be more resistant to pest attacks. Therefore, variety selection must consider the balance between pest resistance and potential production results.